2011
DOI: 10.1042/bj20110302
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D1 mediates bFGF-induced Bcl-2 expression leading to neurite outgrowth in H19-7 cells

Abstract: The purpose of the present study was to investigate the role of PLD (phospholipase D) in bFGF (basic fibroblast growth factor)-induced Bcl-2 expression and to examine whether overexpressed Bcl-2 influences neurite outgrowth in immortalized hippocampal progenitor cells (H19-7 cells). We found that Bcl-2 expression was maximally induced by bFGF within 24 h, and that this effect was reduced by inhibiting PLD1 expression with PLD1 small interfering RNA or by overexpressing DN (dominant-negative)-PLD1, whereas PLD1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…We previously reported that PLD1 is involved in various neuronal signaling pathways and is an important regulator of neuron function (Yoon et al., 2006, Yoon et al., 2012). We also showed that HPCA increased the activity and expression of PLD in various cell types (Hyun et al., 2000, Oh et al., 2006).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that PLD1 is involved in various neuronal signaling pathways and is an important regulator of neuron function (Yoon et al., 2006, Yoon et al., 2012). We also showed that HPCA increased the activity and expression of PLD in various cell types (Hyun et al., 2000, Oh et al., 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, further studies are needed to clarify the relationship between HPCA and PDK1 signaling during neuronal differentiation in NSCs; this could be important for a complete understanding of HPCA-mediated signaling cascade in neurogenesis of NSCs. Our previous studies showed that HPCA played a role in Ca 2+ -dependent PLD activation (Hyun et al., 2000), and PLD1 promotes neurite outgrowth in H19-7 cells (Yoon et al., 2012). As expected, PLD1 is involved in HPCA-mediated neurogenesis and its activation is regulated by HPCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…H19-7 rat embryonic hippocampal cells increase Bcl-2 expression when stimulated by fibroblast growth factor (FGF). Dominantnegative PLD and PLD siRNA inhibit the FGF-induced increase in Bcl-2, suggesting that PLD activity is required for Bcl-2 expression (Yoon et al, 2012). Both studies demonstrate that Bcl-2 transcription increases through the STAT3 transcription factor in a mechanism that requires MAPK activity.…”
Section: Evading Growth Suppressionmentioning
confidence: 99%
“…Thus, the JAK/STAT and mTOR signaling pathways have been implicated in long-distance CNS regeneration. A downstream effector of these pathways is the anti-apoptotic protein Bcl-2 (Sepúlveda et al, 2007;Asomugha et al, 2010;Choi et al, 2011;Yoon et al, 2012). The sustained axonal growth ability observed in retina-superior colliculus cocultures from Bcl-2 transgenic mice translated to the in vivo setting.…”
Section: Overall These Multiple Inhibitors Bind To Their Correspondimentioning
confidence: 99%